Predisposing and precipitating risk factors for delirium in palliative care patients. Issue 4 (August 2020) - Seiler, Annina; Schubert, Maria; Hertler, Caroline; Schettle, Markus; Blum, David; Guckenberger, Matthias; Weller, Michael; Ernst, Jutta; von Känel, Roland; Boettger, Soenke
Abstract: Objective: Delirium is a common complication in palliative care patients, especially in the terminal phase of the illness. To date, evidence regarding risk factors and prognostic outcomes of delirium in this vulnerable population remains sparse. Method: In this prospective observational cohort study at a tertiary care center, 410 palliative care patients were included. Simple and multiple logistic regression models were used to identify associations between predisposing and precipitating factors and delirium in palliative care patients. Results: The prevalence of delirium in this palliative care cohort was 55.9% and reached 93% in the terminally ill. Delirium was associated with prolonged hospitalization ( p < 0.001), increased care requirements ( p < 0.001) and health care costs ( p < 0.001), requirement for institutionalization (OR 0.11; CI 0.069–0.171; p < 0.001), and increased mortality (OR 18.29; CI 8.918–37.530; p < 0.001). Predisposing factors for delirium were male gender (OR 2.19; CI 1.251–3.841; p < 0.01), frailty (OR 15.28; CI 5.885–39.665; p < 0.001), hearing (OR 3.52; CI 1.721–7.210; p < 0.001), visual impairment (OR 3.15; CI 1.765–5.607; p < 0.001), and neoplastic brain disease (OR 3.63; CI 1.033–12.771; p < 0.05). Precipitating factors for delirium were acute renal failure (OR 6.79; CI 1.062–43.405; p < 0.05) and pressure sores (OR 3.66; CI 1.102–12.149; p < 0.05). Significance of results: Our study identified several predisposing and precipitating risk factors for delirium in palliative care patients, some of which can be targeted early and modified to reduce symptom burden.